MOTIVASI MENENTUKAN DAN MERAIH CITA-CITA BAGI REMAJA - Sahabudin Sidik (Asian Journal of Innovation and Entrepreneurship, 2013)
At the present time education is a primary need, education plays an importantrole. At the time of the people racing to get an education as possible, but on the otherhand there are some people who can not be educated appropriately, both from groundlevel and up to a higher level. In addition there are also members of the public who havebeen able to basic education but eventually dropped out of school as well. In the hamletNgaglik, RT 02 RW 04, quite a lot of teenagers who do not continue higher education,teens are choosing to marry young, sober work or migrate to find work. The teens donot have high aspirations for their future. Some teens do not even dare to determinetheir own ideals. This happens due to lack of knowledge about the teen a highereducation and a lackof motivation from the environment. The purpose of this programis to motivate adolescents to be more eager to achieve a promising future. Before theprogram is done, data collection and promulgation done first. The program is conductedonce a meeting for five hours, with details of the activities include the provision ofmaterial, discussions and question and answer. The results achieved in this program isthe youth are not afraid anymore to have high ideals and are willing to seek to achieve.